PEMBANGUNAN KESEHATAN REMAJA SEKOLAH: HUBUNGAN TINGKAT PENGETAHUAN DAN PERILAKU REMAJA PUTRI USIA SEKOLAH DALAM MENCEGAH FLOUR ALBUS DI SMA NEGERI 13 MEDAN - Rajagukguk, Marlina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Flour Albus or Pathological leucorrhoea is vaginal discharge caused by a bacterial infection which is characterized by a lot of fluid, yellow, green or even milky in color, accompanied by complaints (itching, pain, heat) and smell (musty, fishy). The level of knowledge is something that underlies how a person's behavior, especially young women in maintaining the cleanliness of female organs because it can affect young women in the form of decreased self-confidence and disruption of social life. This study aims to determine the relationship between the level of knowledge and behavior of young women in preventing pathological vaginal discharge. This type of research uses a descriptive correlation method with a cross-sectional approach. Based on the results of the research conducted, it is known that the majority of young female respondents live with their parents (93.3%) and live in boarding houses (6.7%). Then based on the occupation of the parents of the respondents Private sector/self-employed (60%), civil servants (18.3), odd jobs (15%), farmers etc. (6.7%). Based on how many children, the 1st child (50.0%), the 2nd child (33.3%), the 3rd child (13.3%) and the 4th child and so on (3.3%). Based on the number of sisters, no sisters (56.7%), 2 sisters (18.3%), 3 sisters (15.0%), more than 3 sisters (10.0%). Respondents who experienced pathological vaginal discharge lived with their parents as many as 56 people (93.3%), the ability of parents based on their work as entrepreneurs was found as many as 36 people (60%) as the first child as many as 30 people (50.0%), based on no sister as many as 34 people (56.7%). Based on the results of the research that has been done, it can be concluded that there is a significant relationship between the level of knowledge and the problem of pathological vaginal discharge of p-value = 0.033, with the level of knowledge experiencing more pathological vaginal discharge. Meanwhile, there was no significant relationship between behavior and pathological vaginal discharge problems of p-value = 0.069 with bad behavior experiencing more pathological vaginal discharge. Dominant knowledge affects the prevention of pathological vaginal discharge.